2014
DOI: 10.1002/ab.21541
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in preschool: The associations between participant roles, social competence, and social preference

Abstract: The different roles of bullying participation (bully, follower, victim, defender of the victim, and outsider) have not been investigated in preschool children. The aims of this study were to use a peer-report measure to assess these roles and to investigate their associations with social competence among pre-schoolers. We also explored whether status among peers, indicated by being socially preferred, mediates the relationship between social competence and bullying roles. Three hundred twenty 3- to 6-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
82
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 68 publications
12
82
2
1
Order By: Relevance
“…We found that defending among aggressors sharing victims (see Figure 1a) was more likely than defending among victims targeted by the same aggressors (see Figure 1b). This suggests that aggressive children in early childhood are already able to support each other and provide affection, even though the supportive aggressive roles of assistant and reinforcer are not clearly defined at this age (Camodeca et al, 2015; Monks & Smith, 2010; Monks et al, 2003). The relative lack of defending among young victims supports the explanation that aggressors are less selective, which implies that victimization would be less likely an enduring experience for most children.…”
Section: Discussionmentioning
confidence: 99%
“…We found that defending among aggressors sharing victims (see Figure 1a) was more likely than defending among victims targeted by the same aggressors (see Figure 1b). This suggests that aggressive children in early childhood are already able to support each other and provide affection, even though the supportive aggressive roles of assistant and reinforcer are not clearly defined at this age (Camodeca et al, 2015; Monks & Smith, 2010; Monks et al, 2003). The relative lack of defending among young victims supports the explanation that aggressors are less selective, which implies that victimization would be less likely an enduring experience for most children.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rose et al () found that peers were rarely involved, during aggressive episodes, in supporting the bully, defending the victim, or watching, other findings pointed to group dynamics similar to those observed for older children and adolescents (Belacchi & Farina, ; Camodeca, Caravita, & Coppola, ; Monks, Ortega Ruiz, & Val, ; Monks, Smith, & Swettenham, ; ). We think that participant roles at this young age deserve to be investigated more deeply to understand the first indications of bullying phenomenon and possible variables which can contribute to its development.…”
Section: Introductionmentioning
confidence: 93%
“…The literature on social preference and bullying in preschool children is more extensive than the literature on emotion regulation and bullying. Social preference has been found to be negatively associated with bullying and positively associated with defending the victim (Camodeca et al, ; Monks et al, ; ). However, fewer and more contrasting results are available for children in the other roles, with followers of the bully, victims, and outsiders showing unclear patterns of social preference (Camodeca et al, ; Monks et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is beyond the scope of this article to fully elucidate the postulations of the Bukowski and Sippola (2001) model, but suffice it to say that greater attention is needed to both intrapersonal and interpersonal factors at the dyadic and group level that contribute to peer victimization subtypes. An example of fruitful efforts in this area may be found within studies addressing various aggression=victimization roles (e.g., bully, defender of the victim, outsider, victim) that peers assume in typical bullying contexts (e.g., Salmivalli, Lagerspetz, Bjö rkqvist, Osterman, & Kaukiainen, 1996) even in preschool (e.g., Camodeca, Caravita, & Coppola, 2014). A second example of rewarding directions include recent studies that have, for example, found associations between adolescents' bullying and likeability as assessed with innovative social network analysis techniques (e.g., Sentse, Kiuru, Veenstra, & Salmivalli, 2014).…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 99%